Analisis Fluktuasi Pemakaian Air Bersih di Pemukiman Desa - Achmad Afandi Oktavianto; Firra Rosariawari (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The need for water in an area is certainly different. Water needs in rural and urban areas are clearly different. This difference in water demand is influenced by water usage, and this difference in water usage will give rise to the value of water fluctuations. This study aims to determine the value of water usage fluctuations in rural residential areas so that water suppliers can know the exact amount of water discharge that will be distributed to customers in the area, in this way it is expected to make the water distribution system more effective, then it is also expected that the water supplier is able to know the number of water losses distributed to make improvements to the network system in the residential area. This research study is located in a residential area of the village, with a research time of 24 hours. From the results of observations in the field which were then calculated, the total debit of water usage per day from a total of 632 customers in the area was 320 m3 / day or 3.70 liters / second. As for the secondary data obtained, the total water distribution to customers in the village settlement area is 5169 m3 / month or 1.99 liters / second for the period April 2023. So that the water loss rate in the area is 46.21%. The peak hour debit is 5.39 liters/second with a water pressure value of 1.8 ATM.